Occupational employment in the not-for-profit sector. - Warren, Zack (Monthly Labor Review, 2008)
The for-profit and not-for-profit sectors differ in regards to the industries with the most employees and the types of jobs that employees most commonly hold; the average wage of each sector is similar, but in a given occupation, the profit sector is generally more highly remunerative